Personal Attributes of Pharmacy Graduates From an Indonesian University as Care Providers - Desak Ernawati; Ya Ping Lee; Bruce Sunderland; Jeff Hughes (Fakultas Farmasi, Universitas Surabaya, 2017)
Objective: Pharmacists’ roles in providing patient care remain limited in Indonesia, hencethis study aimed to determine the preparedness of pharmacy graduates from one university in Indonesia todeliver patient care. Methods: Pharmacy graduates (both registered pharmacists [104] and recent graduateseligible for registration [45]) were sent a validated self-administered survey. The survey sought theirperceptions about whether they had acquired 16 patient care related attributes. Further, it sought theiropinion on the desirability of having those attributes.Data were analysed using SPSS version 22.0. Results:Sixteen of 104 (15.4%) registered pharmacists and 40 of 45 (88.9%) recent pharmacy graduates participatedin the study. More than 50% of participants in both groups were female and most participants were aged intheir 20s. Of the recent pharmacy graduates the majority perceived they had at least partially acquired fourof 16 list attributes. Male and female recent graduates had significantly different beliefs about their leadershipability (p=0.004). In comparison, most registered pharmacists perceived they had 10 out of the 16 listedattributes. Conclusion: The findings of this study suggested that pharmacy graduates should be better preparedto deliver patient care, and that curriculum redesign with expansion of experiential learnings required.